MENINGKATKAN PENJUALAN KALAPA KLOPO DENGAN STRATEGI BAURAN PEMASARAN YANG EFEKTIF (Studi Kalapa Klopo Cabang Mampang Prapatan) - Duwi Kurniawan; Wahyu Nurul Faroh (Journal of Research and Publication Innovation, 2025)
This study aims to identify the most effective marketing mix strategy in increasing consumer demand for Kalapa Klopo. The research method used is qualitative, with the researcher as the main instrument. Data collection techniques are carried out purposively and snowball, with a triangulation approach and inductive data analysis. The results of the study indicate that promotional strategies through social media, especially Instagram, as well as participation in events and bazaars, have proven effective in increasing brand awareness, attracting consumer interest, and driving sales. In addition to promotion, product aspects also play an important role. Consumers are attracted to the quality of fresh coconut, various flavors, and attractive packaging. The implementation of marketing mix strategies in terms of product, price, place, and promotion is considered quite successful, especially in the South Jakarta area and its surroundings. This is reflected in the increase in the number of orders from offices, companies, and various large events. However, there are still a number of challenges, such as limited distribution reach to other areas, the need to improve the taste of certain variants such as brown sugar, and the unavailability of dine-in facilities that limit consumers to take-away services. With improvements in these aspects, Kalapa Klopo has the potential to expand its market and increase customer loyalty.